Evapotranspiration and crop coefficient of adult coffee trees - Lena, Bruno Patias; Flumignan, Danilton Luiz; Faria, Rogério Teixeira (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to determine the evapotranspiration (ET) of adult coffee trees irrigated by sprinkler and drip and under no irrigation, as well as the crop coefficient (Kc) under both water regimes. The experiment was performed in Londrina, PR, Brazil, with the coffee cultivar Iapar 59, from September 2006 to August 2008, with five and six-year-old plants. Evapotranspiration was measured by five weighting lysimeters, two of which were under sprinkler irrigation, one under drip system and two others without irrigation. Irrigation was applied twice a week to maintain soil moisture near field capacity. The crop coefficient was determined by the ratio between ET of the irrigated plants and the reference crop evapotranspiration (ETo). A higher ET mean was found for coffee plants under sprinkler irrigation (3.2 mm day-1), in comparison to the ones under the other treatments, which showed similar means (2.8 mm day-1). Kc values followed the same trend of ET, due to the ET and ETo ratios, with a higher mean for sprinkler irrigation (1), followed by drip irrigation (0.88).